Total current grain mass under alternating electric field of high tension - Bereka, O.; Usenko, S. (Energy and Automation, 2015)
The theoretical position passage bit processes in the grain mass, under an electric field of high tension AC and separated from the dielectric electrode plates that revealed Mathematical formulas given total current bias currents and discharge current.